2000
DOI: 10.1021/jf000956t
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Stability of Carotenoids in the Flowers of Daylily (Hemerocallis disticha) as Affected by Various Treatments

Abstract: The analysis and stability of carotenoids in the flowers of daylily (Hemerocallis disticha) as affected by soaking and drying treatments were studied. The various carotenoids in the flowers of daylily were analyzed using a reversed-phase C(30) HPLC column and a mobile phase of methanol/methylene chloride/2-propanol (89:1:10, v/v/v) with methanol/methylene chloride (45:55, v/v) as sample solvent. Twenty-one pigments were resolved, of which 14 carotenoids were identified, including neoxanthin, violaxanthin, viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 27 publications
7
56
0
Order By: Relevance
“…Table II shows the tentative identification data of carotenoid pigments in tomato. Peak 1 was identified as cis-lutein, which was similar to that reported by Tai and Chen (2000) [19]. Peak 7 was identified as all-trans-lycopene, based on chromatography with added standards and by comparison of the absorption spectra of the unknown peak with the reference standard.…”
Section: Resultssupporting
confidence: 85%
“…Table II shows the tentative identification data of carotenoid pigments in tomato. Peak 1 was identified as cis-lutein, which was similar to that reported by Tai and Chen (2000) [19]. Peak 7 was identified as all-trans-lycopene, based on chromatography with added standards and by comparison of the absorption spectra of the unknown peak with the reference standard.…”
Section: Resultssupporting
confidence: 85%
“…The peak eluted at 31 min was isolated. The absorption maxima of the eluent (414, 436, and 464 nm) were close to those of c-vio reported previously (Tai and Chen, 2000; Table I). The epoxide test indicated that the eluent was 5,6,5Ј,6Ј-diepoxide because the absorption maxima shifted from 414, 436, and 464 nm to 380, 401, and 427 nm, respectively, after the addition of HCl.…”
Section: Identification Of Carotenoidssupporting
confidence: 88%
“…Boiled soybeans had a significantly higher content of daidzin, genistin and genistein than frozen and freeze-dried soybeans. Freezedrying preserved more carotenoids from daylily (Hemerocallis disticha) flowers than air-drying (Tai and Chen, 2000). Finally, one study compared oven-drying with freeze-drying on the formononetin content of red clover.…”
Section: Carotenoidsmentioning
confidence: 99%